Intrahepatic cholestasis of pregnancy (ICP): case report and review of the literature - Keitel, V.; Dröge, C.; Stepanow, S.; Fehm, T.; Mayatepek, E.; Köhrer, K.; Häussinger, D. (Zeitschrift für Gastroenterologie, 2016)
Intrahepatic cholestasis of pregnancy (ICP) represents the most common pregnancy-related liver disease in women. Women frequently present in the third trimester with pruritus and elevated serum bile acid and/or alanine transaminase levels. Clinical symptoms quickly resolve after delivery; however, recurrence in subsequent pregnancies has to be expected. Intrahepatic cholestasis of pregnancy is associated with increased perinatal complications, such as premature delivery, meconium staining of the amniotic fluid, respiratory distress, low Apgar scores, and even stillbirth. The risk for the fetus is significantly increased with maternal serum bile acid levels above 40 µmol/L, which characterize severe ICP. An important factor for ICP development is a rise of gestational hormones leading to cholestasis in genetically predisposed women. Variants in the bile salt export pump (BSEP) and the multidrug resistance protein 3 (MDR3) are most often identified in ICP. Here, we give an overview of the current literature on ICP and present the case of a woman with recurrent severe ICP. A common BSEP polymorphism as well as a rare MDR3 mutation may underlie the development of ICP in our patient. She had a premature delivery with meconium staining of the amniotic fluid. The neonate showed signs of respiratory distress with a low Apgar score. This case emphasizes that women with severe ICP have an increased risk for perinatal complications. Furthermore, severe ICP was associated with a MDR3 mutation, which has already been described in adult patients with liver cirrhosis. Thus, ICP may unmask an underlying MDR3 defect, which may predispose to development of hepatobiliary diseases such as gallstone disease, liver fibrosis/cirrhosis, as well as hepatobiliary malignancies. Therefore, genetic testing should be considered in women with severe as well as early onset ICP. Furthermore, regular follow-up should be discussed for women with genetic variants.
Keywords: Cholestase; Schwangerschaft; Gallensäuren; MDR3; BSEP; Polymorphismen